Glutathionylation Mediates Angiotensin II–Induced eNOS Uncoupling, Amplifying NADPH Oxidase‐Dependent Endothelial Dysfunction. Issue 2 (22nd April 2014) - Galougahi, Keyvan Karimi; Liu, Chia‐Chi; Gentile, Carmine; Kok, Cindy; Nunez, Andrea; Garcia, Alvaro; Fry, Natasha A. S.; Davies, Michael J.; Hawkins, Clare L.; Rasmussen, Helge H.; Figtree, Gemma A.
Abstract : Background: Glutathionylation of endothelial nitric oxide synthase (eNOS) "uncouples" the enzyme, switching its function from nitric oxide (NO) to O2 − generation. We examined whether this reversible redox modification plays a role in angiotensin II (Ang II)‐induced endothelial dysfunction. Methods and Results: Ang II increased eNOS glutathionylation in cultured human umbilical vein endothelial cells (HUVECs), rabbit aorta, and human arteries in vitro. This was associated with decreased NO bioavailability and eNOS activity as well as increased O2 − generation. Ang II‐induced decrease in eNOS activity was mediated by glutathionylation, as shown by restoration of function by glutaredoxin‐1. Moreover, Ang II‐induced increase in O2 − and decrease in NO were abolished in HUVECs transiently transfected, with mutant eNOS rendered resistant to glutathionylation. Ang II effects were nicotinamide adenine dinucleotide phosphate (NADPH) oxidase dependent because preincubation with gp 91ds‐tat, an inhibitor of NADPH oxidase, abolished the increase in eNOS glutathionylation and loss of eNOS activity. Functional significance of glutathionylation in intact vessels was supported by Ang II‐induced impairment of endothelium‐dependent vasorelaxation that was abolished by the disulfide reducing agent, dithiothreitol. Furthermore, attenuation of Ang II signaling in vivo by administration of an angiotensin converting enzyme (ACE) inhibitor reduced eNOS glutathionylation, increased NO, diminished O2 −, improved endothelium‐dependent vasorelaxation and reduced blood pressure. Conclusions: Uncoupling of eNOS by glutathionylation is a key mediator of Ang II‐induced endothelial dysfunction, and its reversal is a mechanism for cardiovascular protection by ACE inhibition. We suggest that Ang II‐induced O2 − generation in endothelial cells, although dependent on NADPH oxidase, is amplified by glutathionylation‐dependent eNOS uncoupling.